A IMPORTÂNCIA DA BIOSSEGURANÇA NOS LABORATÓRIOS - Silveira, Camila Cristina Sauder Da; Krever, Ivã Augusto; Norbert, Leonardo; Comparsi, Bruna (Salão do Conhecimento, 2019)
Projeto de extensão realizado no curso de Biomedicina da Unijuí